The Role of MYCN in Symmetric vs. Asymmetric Cell Division of Human Neuroblastoma Cells - Izumi, Hideki; Kaneko, Yasuhiko; Nakagawara, Akira (Frontiers in Oncology, 2020)
Asymmetric cell division (ACD) is an important physiological event in the development of various organisms and maintenance of tissue homeostasis. ACD produces two different cells in a single cell division: a stem/progenitor cell and differentiated cell. Although the balance between self-renewal and differentiation is precisely controlled, disruptions to ACD and/or enhancements in the self-renewal division (symmetric cell division: SCD) of stem cells resulted in the formation of tumors in Drosophila neuroblasts. ACD is now regarded as one of the characteristics of human cancer stem cells, and is a driving force for cancer cell heterogeneity. We recently reported that MYCN controls the balance between ACD and SCD in human neuroblastoma cells. In this mini-review, we discuss the mechanisms underlying MYCN-mediated cell division fate.